The law-making process - Zander, Michael (Cambridge University, 2013)
As a critical analysis of all aspects of the law-making process, this book has no equal. In the fourteen years since it first appeared, it has filled a yawning gap in the requirements of law students and others taking introductory courses on the legal system. It presents a large number of original texts from a variety of sources - cases, official reports, articles, books, speeches and surveys, laced with the author's own informed reflections on the subject. The new edition of this highly popular text has been fully updated to include recent developments in case law and statutes, including Pepper v Hart and the 1992 Hansard Society's important report on the Legislative Process. It has been expanded especially in the chapters on legislation and European Community law.